Keselamatan Diri dalam Qurban Idul Adha 1441 H sebagai Bentuk Pengabdian kepada Masyarakat Politeknik Penerbangan Palembang - Anton Abdullah; Wildan Nugraha; Fitri Masitoh; Sutiyo Sutiyo; Rinto Astutik (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2020)
The target and output of this activity are to implement the Tridharma of Higher Education, community service for lecturers in the Palembang Aviation Polytechnic environment, South Sumatra. The activity method used is 1) religious lectures, namely spiritual guidance to the Aviation Polytechnic extended family and local residents; 2) The lecture in which the resource person explained to the Aviation Polytechnic extended family and local residents about the wisdom of sacrificing and following the shari'ah of Prophet Ibrahim AS, fostering awareness and participation of the Aviation Polytechnic family and local residents in fostering a love for others in the manifestation of gratitude and piety Allah SWT; and 3) evidence-based learning, in which the "sacrifices" and the implementation team were invited to work together on how to collect, slaughter, and distribute sacrificial animals. The results obtained from this activity can make the implementation team, the Aviation Polytechnic extended family, and residents 1) follow the shari'ah of Prophet Ibrahim AS; 2) Growing awareness and participation of Muslims (lecturers) in fostering a love for others in the manifestation of taqwa to Allah SWT; 3) Serve the community in strengthening ties of friendship to establish ukuwah Islamiah among residents.